THE ROLE OF A TECHNOLOGY-ENRICHED “TEACHING MEDIA” COURSE IN IMPROVING INDONESIAN SCIENCE STUDENT TEACHERS’ TECHNOLOGY INTEGRATION - Rika Rafikah Agustin; Liliasari Liliasari; Parlindungan Sinaga; Diana Rochintaniawati (Jurnal Pengajaran MIPA, 2020)
Technological pedagogical content knowledge (TPACK) has been widely used as a framework to assess teachers’ ability to integrate technology into their lessons. This study investigated the role of a technology-enriched “Teaching Media” course on science student teachers’ TPACK and the subscales contributing to the TPACK improvement. The participants were 21 science student teachers enrolled in a “Teaching Media” course. The science student teachers’ TPACK was assessed using a set of multiple-choice tests consisting of 34 questions. Normalized-gain (N-Gain) value was used to measure science student teachers’ TPACK improvement after completing the course. The contribution of each subscale to TPACK was analyzed using partial least squares (PLS). The finding of the study reveals that there is a moderate improvement of science student teachers’ TPACK after completing the technology-enriched “Teaching Media” course. Analysis of the contribution amongst TPACK subscales showed that technological knowledge and other technology-related knowledge significantly contribute to the improvement of science student teachers’ TPACK.